Protective effects of high-potency FMDV O1 Manisa monovalent vaccine in cattle challenged with FMDV O/SKR/2010 at 7 or 4 days post vaccination. Issue 38 (12th September 2017) - Horsington, Jacquelyn; Perez, Claudia Beascoechea; Maradei, Eduardo; Novo, Sabrina Galdo; Gonzales, Jose L.; Singanallur, Nagendrakumar B.; Bonastre, Paula; Vosloo, Wilna
Abstract: Serotype O foot-and-mouth disease (FMD) virus belonging to the SEA topotype continues to be a significant problem in the Eastern Asia region, with outbreaks in Japan and South Korea resulting in the culling of over 3.5 million cattle and pigs in recent years. High-potency O1 Manisa vaccine was previously shown to provide protection in cattle 21 days post vaccination (dpv) following challenge with a representative virus, O/SKR/2010. This study tested the ability of the O1 Manisa vaccine to protect cattle from infection and disease with the O/SKR/2010 virus within just 4 or 7 days post vaccination. The vaccine protected 50% of cattle from clinical disease when administered 7 days prior to challenge, but was not protective with just 4 days between vaccination and challenge. Viraemia was significantly reduced in animals challenged 7 dpv but not 4 dpv, compared to unvaccinated controls, however, there were no effects on the level of virus detected in nasal and oral secretions regardless of vaccination time. The level of neutralising antibodies detected in cattle challenged 7 dpv correlated with protection from clinical disease. All animals seroconverted to FMDV non-structural proteins, suggesting no sterile protection. An equal number of animals became persistently infected in both vaccine groups. The results indicated that high-potency O1 Manisa vaccine administered just 7 days prior to challenge should provide partial protection of cattle if an outbreak of O/SKR/2010, or related viruses, occurs, and would be useful to limit spread of FMDV when used in conjunction with other control measures.